St. Francis of Assisi: Bioethics in European Middle Ages - Zagorac, Ivana (Array, 2012)
Even the fiercest critics of Christianity, who perceive it as the source of the global ecological crisis we are facing today, revere a great Christian saint, namely St. Francis of Assisi, due to his alternative reading of the interrelation between Man, Nature and God. The paper discusses the basic elements of the life of St. Francis and his message of love for all Creations, and his consequent advocacy of all-embracing egalitarianism in our moral actions. Considering that St. Francis is a popular figure in contemporary bioethical discussions, the paper also briefly examines the compatibility of his message with different bioethical concepts. The paper shows that all the above concepts prove to be too limited to encompass St. Francis’s lived sensibility. In closing, the latter is contextualised within the framework of integrative bioethics.